The Beautiful Tree - James Tooley (Penguin India, 2009)
The Beautiful Tree movingly uncovers the efforts of poor communities in education, and finds competent, committed entrepreneurs who have started schools catering to slum children. He discovers young, engaged teachers, passionate entrepreneurs, and teaching models that work to ensure that students are engaged and learning. He finds that even among the unrecognized private schools, average teacher attendance, and English and maths proficiency surpass the apathetic government school system.This is a passionate and engaging account of the children, parents, teachers, and entrepreneurs who Tooley encounters in the face of staunch government denial that these schools actually exist. They taught him that the poor are not waiting for educational handouts-they are building their own schools and learning to save themselves.